The Nature and Framework of the Situation of Journalists and their Discrimination Under International Law - Bayinat Basha Al Bajali, Abul Firdaus (International Journal of Psychosocial Rehabilitation, 2021)
This study dealt with the issue of journalists in the following demands: the concept of journalists and their classifications. distinguishing journalists from other media professionals. This research deals with the press, its freedoms and controls, and the links of the press: their nature, origins, protection, and impact on societal, human, and cultural development, and their legal rules. Because they have occupied a large and important space in the most prominent fields of contemporary life, especially open-source social media, and they have covered most aspects of human, natural, and cosmic activity, it was worth studying all their aspects to clarify the position of Sharia and the law on them and their rulings on them. There is no doubt about the necessity and necessity of submitting them to their controls to ensure optimal benefit from them, as they are among the services that are indispensable in our contemporary time. Whereas the media and the press are of such vitality and importance, I did in this subject as required by the requirements of the study. This study was based on the extrapolation of the issues in which the opinions of scholars varied according to the multiplicity of factors related to the edge, according to an applied analytical methodology.